Two-point method for arterial local pulse wave velocity measurement by means of ultrasonic RF signal processing - TRAWIŃSKI, Zbigniew (Archives of Acoustics, 2013)
The aim of this paper is to describe a non-invasive method of examination of the local pulse wave velocity. The measurements were carried out in the model of the artery immersed in a water tank. Two synchronized ultrasonic apparatus VED with the ultrasonic radio frequency echoes acquisition system were used for evaluation of the arterial elasticity. The zero-crossing method was used for determination of the diameter changes of the artery model. The transit time between the waveforms of instant artery diameter was measured at two points of the artery model, separated by the distance of 5 cm. The transit time was determined using the criteria of similarity of the first derivatives of the raising slopes of the curves describing instant vessel's diameter changes. The pulse wave velocity obtained by the proposed two-point method was compared with the results obtained by the one-point method based on the modified Bramwell-Hill relation.